'It was hard before and it's even harder now': The impact of COVID-19 on Australia's live music and arts entertainment industries. Issue Volume 21:Number 2(2021)Special Issue:Part 2 (31st December 2022) - Nelligan, Kat; Nelligan, Pariece
Abstract : This Riff article offers reflections on the impact of COVID-19 on the arts and entertainment industries in Australia, with a specific focus on the music industry. The pandemic has placed added financial and psychological strain on the industry's workers and performing artists, many of whom were already struggling emotionally with financial instability and job insecurity prior to the pandemic. The federal government's inadequate financial support for arts workers, and its failure to protect Australia's cultural and economic assets of live music and entertainment during the pandemic, are discussed. There is a need for a COVID-19 recovery plan that addresses the impacts of the pandemic and pre-existing issues of financial instability as well as the federal government's undervaluing and underfunding of arts industries in Australia. The article is written from the perspective of the authors' personal experiences as creative practitioners and researchers in the creative industries, and is based on media articles and research reports published prior to and during the pandemic (2018–2021).